Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 201253 by mathlove last updated on 02/Dec/23

find the sum of n terms of the serice  s_n =5+11+19+29+41+..........

findthesumofntermsofthesericesn=5+11+19+29+41+..........

Answered by Rasheed.Sindhi last updated on 02/Dec/23

(4+1)+(9+2)+(16+3)+(25+4)+..  (2^2 +1)(3^2 +2)+(4^2 +3)+(5^2 +4)+...  General term: (k+1)^2 +k                                 =k^2 +3k+1  Σ_(k=1) ^n (k^2 +3k+1)  =Σ_(k=1) ^(n) k^2 +3Σ_(k=1) ^(n) k+Σ_(k=1) ^(n) 1    =((n(n+1)(2n+1))/6)+3(((n(n+1))/2))+n  =((n(n+1)(2n+1)+9n(n+1)+6n)/6)  =((n(n+1)(2n+1+9)+6n)/6)  =((n(n+1)(2n+10)+6n)/6)  =((n(n+1)(n+5)+3n)/3)  =((n(n^2 +6n+5)+3n)/3)  =((n(n^2 +6n+5+3))/3)  =((n(n^2 +6n+8))/3)  =((n(n+2)(n+4))/3)

(4+1)+(9+2)+(16+3)+(25+4)+..(22+1)(32+2)+(42+3)+(52+4)+...Generalterm:(k+1)2+k=k2+3k+1nk=1(k2+3k+1)=Σnk=1k2+3Σnk=1k+Σnk=11=n(n+1)(2n+1)6+3(n(n+1)2)+n=n(n+1)(2n+1)+9n(n+1)+6n6=n(n+1)(2n+1+9)+6n6=n(n+1)(2n+10)+6n6=n(n+1)(n+5)+3n3=n(n2+6n+5)+3n3=n(n2+6n+5+3)3=n(n2+6n+8)3=n(n+2)(n+4)3

Commented by mathlove last updated on 03/Dec/23

thanks

thanks

Answered by Rasheed.Sindhi last updated on 07/Dec/23

s_n =5+11+19+29+41+..........      =(4+1)+(9+2)+(16+3)+(25+4)+...     =(4+9+16+...)+(1+2+3+4+...)     =(1^2 +2^2 +3^2 +4^2 +..._((n+1) terms) −1)+(1+2+3+4+..._(n terms) )  Formulas:  1+2+3+...+N=((N(N+1))/2)  1^2 +2^2 +3^2 +...+N^2 =((N(N+1)(N+2)(2N+1))/6)    =(((n+1)(n+2)(2(n+1)+1))/6)−1+((n(n+1))/2)    =(((n+1)(n+2)(2n+3))/6)−1+((n(n+1))/2)    =(((n+1)(n+2)(2n+3)−6+3n(n+1))/6)    =(((n+1)(n+2)(2n+3)+3n(n+1)−6)/6)    =(((n+1){(n+2)(2n+3)+3n}−6)/6)    =(((n+1){2n^2 +3n+4n+6+3n}−6)/6)    =(((n+1)(2n^2 +10n+6)−6)/6)    =((2n^3 +10n^2 +6n+2n^2 +10n+6−6)/6)    =((2n^3 +12n^2 +16n)/6)    =((n(n^2 +6n+8))/3)  =((n(n+2)(n+4))/3) (✓)

sn=5+11+19+29+41+..........=(4+1)+(9+2)+(16+3)+(25+4)+...=(4+9+16+...)+(1+2+3+4+...)=(12+22+32+42+...(n+1)terms1)+(1+2+3+4+...nterms)Formulas:1+2+3+...+N=N(N+1)212+22+32+...+N2=N(N+1)(N+2)(2N+1)6=(n+1)(n+2)(2(n+1)+1)61+n(n+1)2=(n+1)(n+2)(2n+3)61+n(n+1)2=(n+1)(n+2)(2n+3)6+3n(n+1)6=(n+1)(n+2)(2n+3)+3n(n+1)66=(n+1){(n+2)(2n+3)+3n}66=(n+1){2n2+3n+4n+6+3n}66=(n+1)(2n2+10n+6)66=2n3+10n2+6n+2n2+10n+666=2n3+12n2+16n6=n(n2+6n+8)3=n(n+2)(n+4)3()

Commented by Rasheed.Sindhi last updated on 07/Dec/23

 Now OK!

NowOK!

Terms of Service

Privacy Policy

Contact: info@tinkutara.com